2018
DOI: 10.1007/s11999.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Compression Reduces Bleeding-related Readmissions and Wound Complications After THA and TKA

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…A prospective clinical study of 632 primary TJA patients evaluated the best combination between mechanical treatment (compression) and pharmacological chemoprophylaxis (aspirin and/or low molecular weight heparin) to prevent postoperative thromboembolic events (Table 5) [193].…”
Section: Resultsmentioning
confidence: 99%
“…A prospective clinical study of 632 primary TJA patients evaluated the best combination between mechanical treatment (compression) and pharmacological chemoprophylaxis (aspirin and/or low molecular weight heparin) to prevent postoperative thromboembolic events (Table 5) [193].…”
Section: Resultsmentioning
confidence: 99%
“…Chemoprophylaxis and pneumatic compression devices were both given "grade 1" recommendations, which denotes there was certainty that the benefits of these treatments outweighed the potential risks [24]. No subsequent guidelines have been published, but there is a fair amount of research that can aid in supporting the use of ambulatory compression pumps [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The higher risk of bleeding events with stronger chemoprophylaxis has led many surgeons and researchers toward the use of ASA -based VTE prophylaxis regimens [6,12,13,25]. Parvizi et al reported a 0.1% to 0.3% incidence of VTE in a low-risk VTE population undergoing lower extremity arthroplasty with ASA chemoprophylaxis [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations